Immobilization of recognition elements on a self-assembled monolayers bio-platform - Julia Constanza Reyes-Cuellar (Dyna, 2017)
Tailored materials formed by spontaneous two-dimensional arrangement of 3-aminopropyltriethoxysilane self-assembled monolayer on glass (amino-functionalized glass) has been exploited to attach biomolecules in well-organized structures useful in biosensing.  Succinimidyl ester of both unpolymerized diacetylene liposome (NHS-DA-liposome) layer and PEGylated biotin (Bt-PEG-NHS) matrix were covalently bonded to the amino-functionalized glass by the NHS linker, and exposed to either Tyrosinase (Ty) or Streptavidin (SAV) solution. The interaction between Ty and polymerized NHS-PDA-liposome transformed the planarity of the PDA backbone, and a blue-to-red transition occurred; Bt-PEG attached to the fluorescent-SAV by bioaffinity.  Sensing capability of bioplatform systems was evaluated by Uv-vis spectroscopy or fluorescence microscopy. Biomolecule functionalized SAMs retained the recognition potential of colorimetric Ty-PDA-liposome after biological interaction, and also facilitated the fabrication of a protein-resistant matrix with a particular affinity property.  This surface chemistry is accessible to depositing proteins on both SAM-coated glass surface, and tethered to SAM, resulting in optical bioplatform arrays.